LAYANAN PENGUKURAN TINGKAT KINERJA WAROENG STEAK AND SHAKE YOGYAKARTA DENGAN METODE IMPORTANCE PERFORMANCE ANALYSIS - , NASRUDIN N.I., Dr. Ir. Didik Purwadi, M.Ec ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Waroeng Steak and Shake has significantly improvement since 2000th until 2014th . Now it has 59 outlet branches in 18 cities in Indonesia and million hundred rupiah omzet every month. The significantly improvement of Waroeng Steak and Shake need to be evaluated. There are phenomenon in Yogyakarta, some of outlet are less product sold out and the costumer are low, even it almost bankrupt. This research take a sample in three outlet branch, in Demangan, Taman Siswa, and Colombo. The outcome of this research is to know and detect about which atributes that need to be improved optimally as a main priority in service performance. About 100 people are choosen as a respondent. The research use importance performance analysis as a basic methode. The result of this research show that there are some atributes need to be evaluated as a main priority